Languages: From Formal to Natural Essays Dedicated to Nissim Francez on the Occasion of His 65th Birthday - Grumberg, Orna; Kaminski, Michael; Katz, Shmuel; Wintner, Shuly (Programming and Software Engineering, 2009)
This Festschrift volume, published in honor of Nissim Francez on the occasion of his 65th birthday, contains 15 papers, written by friends and colleagues, many of whom congregated at a celebratory symposium held on May 24-25, 2009, in Haifa, Israel. The theme of the symposium was Languages: From Formal to Natural, reflecting the focus of Nissim Francez' research career, which started in program verification and the semantics of programming languages and later concentrated on natural languages and computational linguistics. The papers included in this volume cover the entire spectrum of this field of research.